1999
DOI: 10.1074/jbc.274.5.2645
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Thromboxane Receptor α, the Predominant Isoform Expressed in Human Platelets

Abstract: A single gene encodes the human thromboxane receptor (TP), of which there are two identified splice variants, ␣ and ␤. Both isoforms are rapidly phosphorylated in response to thromboxane agonists when overexpressed in human embryonic kidney 293 cells; this phenomenon is only slightly altered by inhibitors of protein kinase C. Pharmacological studies have defined two classes of TP in human platelets; sites that bind the agonist I-BOP with high affinity support platelet shape change. Low affinity sites, which ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 39 publications
5
94
0
1
Order By: Relevance
“…Additional immunofluorescence studies, employing TP isoform specific antibodies directed to peptide sequences within the unique C-tail domains of TPα and TPβ, also confirmed the expression and cellular localisation of the TP receptors [38,39]. Taken together, these studies investigating the expression and tissue distribution of the TPα and TPβ receptors indicate that they are subject to differential expression and regulation [34].…”
Section: Expression Of the Tp Isoformsmentioning
confidence: 73%
See 1 more Smart Citation
“…Additional immunofluorescence studies, employing TP isoform specific antibodies directed to peptide sequences within the unique C-tail domains of TPα and TPβ, also confirmed the expression and cellular localisation of the TP receptors [38,39]. Taken together, these studies investigating the expression and tissue distribution of the TPα and TPβ receptors indicate that they are subject to differential expression and regulation [34].…”
Section: Expression Of the Tp Isoformsmentioning
confidence: 73%
“…Consistent with this hypothesis, based on observations that TP isoform specific antibodies permitted detection of TPα, but not TPβ in human platelets, Habib et al, [39] have proposed that…”
Section: Tp Receptor Desensitizationmentioning
confidence: 91%
“…Indeed, there is a growing body of evidence that illustrates interactions between 8-iso PGF 2a and TP receptors. In human platelets 8-iso PGF 2a binds to TP receptors, although its interaction at these sites appears complex and has not been fully de®ned Minuz et al, 1998;Habib et al, 1999). Using platelet-rich plasma, Pratico et al (1996) have shown that 8-iso PGF 2a can activate human platelets to induce shape change and facilitate the proaggregatory actions of other full agonists but cannot itself induce full aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this phenomenon could not be attributed to TP receptor activation. However, 8-iso PGF 2a was subsequently (Habib et al, 1999) shown to bind a speci®c site on TPa receptors and to trigger signal transduction distinct from thromboxane (Takahara et al, 1990). Using whole blood, we were not able to reliably determine e ects on shape change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation